Cartografías del feminismo mexicano1970-2000 (Andamios, Revista de Investigación Social, 2019)
Reseña del libro: García, N. N., Millán, M., Pech, C. (Coords). (2018). Cartografías del feminismo mexicano 1970-2000. México: UACM.